Collaborative Governance Berbasis Kearifan Lokal dalam Mewujudkan Desa Mandiri: Integrasi IDM dan SDGs Desa - P, Resky Amalia; M, Nursafitra (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2026)
This study aims to develop a collaborative governance model based on local wisdom to realize independent villages through the integration of the Village Development Index (IDM) and the Village SDGs. This research is motivated by the increasing achievements of village development in Indonesia since the implementation of the village fund policy, but this is not evenly distributed because most villages are still in the developing and developed categories. This condition indicates that the village development process still faces challenges in increasing independence in a sustainable manner, especially in optimizing collaboration between actors and utilizing local wisdom. Various previous studies have examined village development through participatory approaches and collaborative governance, but their implementation still tends to be partial and has not been able to optimally integrate local potential. Furthermore, the integration between the IDM as an indicator of development achievements and the Village SDGs as a direction for sustainable development has not been fully integrated into an integrated framework in village development practices. The study used a qualitative approach with a case study design in Wajo Regency. Data were obtained through interviews, observations, and documentation, then analyzed using an interactive analysis model with reference to the collaborative governance framework. The results show that the success of collaboration is determined by four main factors: collective leadership, material and non-material incentives, interdependence between actors, and the ability to face uncertainty. Leadership involving formal and informal actors can increase community trust and participation, while incentives and local wisdom values, such as mutual cooperation, serve as drivers for sustained engagement. Synergy between actors strengthens collective capacity in village development, despite persistent challenges in human resources, budgeting, and coordination. This research yields an integrative collaborative governance model as a strategy to accelerate the realization of sustainable, independent villages.